(3GdaQhb GddZhjI (B/s - (3GdYScQj, GdMSf Hf YHO Gddg Hf Sgd,s (3Jhaj HYO (B395 (3gLQjs; (3GdHGQhOj , YeGOs ((3GdbGgQI (B:s (3OGQ GdJhajbjI ddJQGK,s, 2010)
(3gPG GdcJGH gh hGMO ef GdcJH GdJj JQcgG dfG YdeGA GdYQHjI, GdPjf hbahG MjGJge Ydi NOeI GddZI GdYQHjI hUjGfI eaQOGJgG ef GddMf hGdNWC(B.s
(3HHdjhLQGajI (B: (3U(B. 428-443.s
Keywords: (3GddZI GdYQHjIs -- (3CdaGXs; (3GddZI GdYQHjIs -- (3GTJbGbs